Inhibition of c-Abl suppresses the proliferation, invasion and migration of glioma cells - Fengqi Zhang; Xianzhi Liu (BMC Cancer)
Abstract Background The proto-oncogene c-Abl has been implicated in tumor progression across multiple cancer types, but its role in glioma remains poorly understood. This study aimed to investigate the function of c-Abl in glioma progression and assess its potential as a therapeutic target. Methods High-throughput RNA sequencing was conducted on U-87 glioma cells following c-Abl knockdown. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were used to explore the biological pathways involved. Functional assays, including MTS for cell viability, Transwell assays for invasion and migration, and immunofluorescence (IF), were performed to evaluate cellular behavior in vitro. In vivo, a mouse xenograft model was treated with the c-Abl inhibitor dasatinib, and tumor progression was assessed by hematoxylin and eosin (HE) and immunohistochemistry (IHC) staining. Results RNA sequencing revealed that differentially expressed genes (DEGs) following c-Abl knockdown were significantly enriched in cell cycle-related pathways. Silencing c-Abl reduced U-87 cell viability by 7% at 48 h and 15.3% at 72 h (P < 0.01 and P < 0.0001) and suppressed cell invasion and migration by 48.3% and 40.6%, respectively (P < 0.001). Knockdown also reduced expression of Ki67, Snail, and Vimentin. In vivo, dasatinib treatment decreased tumor volume by 51.8% by day 24 (P < 0.001), increased necrotic area (P < 0.01), and downregulated epithelial-mesenchymal transition (EMT) markers (P < 0.05). Conclusions c-Abl contributes to glioma cell proliferation, invasion, and migration, likely through pathways related to cell cycle and EMT. These findings support c-Abl as a promising therapeutic target in glioma treatment.